Charity account in Islamic financial institutions: creating a defined Sharīʻah standard - Salim Ali Al-Ali (ISRA International Journal of Islamic Finance, 2022)
Purpose- This article seeks to propose a defined set of Sharīʿah standards and guidelines for the charity account in order to provide clear guidance to Islamic financial institutions (IFIs) and eventually create a standardised practice in the management of the charity account by IFIs worldwide. Design/methodology/approach - This article is based on a literature review regarding the origin and concept of the charity account for IFIs. It makes reference to various primary Sharīʿah sources and contemporary Sharīʿah standards pertaining to impermissible income as it relates to the charity account. It also analyses secondary sources of reference, in particular research papers and case studies on the same subject matter. Findings - This article proposes relevant Sharīʿah standards required for the better functioning and standardisation of the charity account application by IFIs. Research limitations/implications - This article will help IFIs, standard-setting bodies and regulators to develop a defined charity account framework. It also addresses the gaps discussed in past research and case studies that have not been resolved to date, particularly on the determination and management of charity accounts at the level of IFIs. Practical implications - The charity account will be better controlled and thus eliminating potential reputational issues arising from collecting and disbursing commitment to donate amounts (CDA). Social implications - The charity account distribution will be better managed and thus of more benefit to the society and recipients. Originality/value - This article promotes the idea of standardisation in the practices of charity accounts, especially in terms of sources and disbursement.
Keywords: 330; Charity account; Donation; Islamic banks; Islamic finance; Late payment penalty; Sharīʿah compliance; Sharīʿah non-compliant earnings